Effects of various water storage methods on plantation of Greek juniper (Juniperus excelsa M. B.) - Mohammad Hossein Sadeghzadeh Hallaj; Hashem Keneshloo; Mostafa Khoshnevis; Majid Hassani; Pejman Parhizkar (تحقیقات جنگل و صنوبر ایران, 2017)
This research was carried out in Sirachal Research Station in order to identify the best method for Greek juniper (Juniperus excelsa M. B.) afforestation as one of the most important forest species in Iran. Three year-old juniper saplings were transported to Sirachal and were planted in a Split-Plot Randomized Block Design with water harvesting (in 5 treatments including using organs of native plants and shrubs at the bottom of pits, using 1×1 m plastic film at the surface of pits, using Aquasorb polymers mixed with the pits soil, semi-circular bonds and control) as main factor and shading (in 2 level of using tree sprouts as artificial shading and control) as secondary factor in 3 replication and 16 saplings per replication. Measured variables were survival, collar diameter, height, and crown area and sapling vitality at the end of growing season of 2015 and 2016. Results showed that rainwater harvesting had significant effect on survival juniper saplings for both 2014 and 2015 years and current annual increment of collar diameter. The highest value of these parameters was noticed for plastic film treatment though the highest decrease of survival from 2014 to 2015 was noticed for this treatment too. Both rainwater harvesting and shading had no significant effect on height, crown area, vitality and their changes during the studied years. Overall, results confirmed the possibility of rainfed afforestation of Greek juniper in high altitude of Southern Alborz Mountain. To achieve this goal, usage of nylon at the surface of plantation pits is recommended. There is no need to use artificial shading for planted saplings.